Performance analysis of commercial rapid tests for serum troponin detection - Ferreira,Raquel Ida (2020)
ABSTRACT Introduction: Rapid tests represent an important diagnostic tool, providing results in a short period of time and eliminating the use of large automated equipment. Objective: To evaluate the performance of five rapid test kits for troponin I detection in serum. Materials and methods: Samples from 100 patients with suspected acute myocardial infarction (AMI) were selected from a hospital in Barbacena, MG, Brazil. They were tested in the five troponin I commercial rapid test kits and the results were compared with the study reference method (quantitative chemiluminescent immunoassay). Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and correlation coefficients of the rapid tests against the reference method were defined. Results: The kits from Abon®, Interteck®, Medtest® and Wama® presented the same performance, reaching equal levels of sensitivity (98.08%), specificity (100%), PPV (100%), NPV (97.96%), and correlation coefficient (0.99). The Eco Diagnostica® kit presented lower sensitivity (82.69%), low correlation coefficient (0.91) and NPV (84.21%), not reaching ideal levels even though lying within the confidence interval. Discussion: The results obtained with the Abon®, Interteck®, Medtest® and Wama® test kits corroborate pre-existing literature data on the diagnostic accuracy of rapid tests for troponin detection. These tests are allowed for immediate decision making by physicians and can be used to reduce unnecessary hospitalization time and costs associated with a suspected AMI. Conclusion: The kits from Abon®, Interteck®, Medtest® and Wama® showed excellent diagnostic performance, what makes them an important diagnostic tool in smaller laboratories without automated equipment.